PENGARUH KUALITAS PELAYANAN DAN PENGEMASAN DAYA TARIK WISATA TERHADAP KEPUASAN WISATAWAN DI NGEBEL PONOROGO - Kaukabilla A.P; Abdul Kholiq (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Ngebel Lake is a superior nature tourism in Ponorogo Regency. The lack of tourist attractions in this district made the local government strongly asked to increase tourism potential in the village of Ngebel. Facilities development and service improvement continue to be carried out in order to attract tourists. This study discusses the quality of service and the packaging of tourist attractions towards the decision of a visit as well as its consideration of tourist satisfaction. The number of samples used was 100 respondents taken from the number of tourists. From the data obtained from observations, documentation, direct interviews and filling out questionnaires. Multiple regression analysis was performed to determine the effect of the independent variables on the dependent variable. The results showed that there were positive and significant differences between the variables of service quality and tourist attraction packaging towards the decision of the visit and its consideration on tourist satisfaction.Telaga Ngebel merupakan tempat wisata alam unggulan di Kabupaten Ponorogo. Minimnya tempat wisata di kabupaten ini, menjadikan pemerintah daerah berupaya untuk meningkatkan potensi wisata di telaga Ngebel. Pengembangan fasilitas dan peningkatan pelayanan dilakukan demi menarik minat wisatawan. Penelitian ini bertujuan untuk mengetahui pengaruh kualitas pelayanan dan pengemasan daya tarik wisata terhadap kepuasan wisatawan. Pendekatan yang digunakan yaitu deksriptif kuantitatif dengan sampel yang digunakan sebanyak 100 responden yang diambil dari populasi wisatawan. Adapun data diperoleh dari observasi, dokumentasi, wawancara langsung dan pengisian kuisioner. Analisis multipel regresi dilakukan untuk menentukan pengaruh independent variable terhadap dependen variable. Hasil penelitian menunjukan bahwa terdapat pengaruh yang positif dan signifikan antara variable kualitas pelayanan dan pengemasan daya tarik wisata terhadap kepuasan wisatawan.